A visão encarnada do espectador: Formas de perceber, habitar e criar paisagens: The embodied view of the spectator: Ways to perceive, inhabit and create landscapes (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The theater building builds professional and human relationships, which develop a unique transit between this building and the city that houses it. This perspective provided a unique concept of Scenography. The theoretical foundation is centered on the epistemological study that Michel Foucault undertook, recognizing in the 16th century the cognitive action of “spatializing knowledge”, which connects the microcosm to the macrocosm. This cognitive “spatialization” will be considered according to the physical and virtual spaces. The virtual will be analyzed using the digital platform, which allows theatrical performances and audiences to be found in streets and squares recreating the containment rules.
Keywords: Theater Building; City; Physical Space; Virtual Space